2013
DOI: 10.1002/mrd.22232
|View full text |Cite
|
Sign up to set email alerts
|

Defining the neighborhoods that escort the oocyte through its early life events and into a functional follicle

Abstract: The ovary functions to chaperone the most precious cargo for female individuals, the oocyte, to allow the passage of genetic material to subsequent generations. Within the ovary, single oocytes are surrounded by a legion of granulosa cells inside each follicle. These two cell types depend upon one another to support follicle formation and oocyte survival. The infrastructure and events that work together to ultimately form these functional follicles within the ovary are unprecedented, given that the oocyte is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 175 publications
(246 reference statements)
0
15
0
Order By: Relevance
“…Both PKA and MAPK signal transduction pathways were observed to be involved in the junctional communication between the cumulus/granulosa cells and the oocyte and the somatic cells of the follicle. Communication is essential for the growing oocyte and has a role in supplying nutrients to the maturing oocyte [ 35 ]. Western-blot analyses have revealed a significantly reduced phosphorylation of a MAP protein, the extracellular signal-regulated kinases (ERK1/2) in ZP3-KO MII oocytes when compared with wild-type oocytes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both PKA and MAPK signal transduction pathways were observed to be involved in the junctional communication between the cumulus/granulosa cells and the oocyte and the somatic cells of the follicle. Communication is essential for the growing oocyte and has a role in supplying nutrients to the maturing oocyte [ 35 ]. Western-blot analyses have revealed a significantly reduced phosphorylation of a MAP protein, the extracellular signal-regulated kinases (ERK1/2) in ZP3-KO MII oocytes when compared with wild-type oocytes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These synchronously enter meiosis and progress to diplotene of prophase I where they become arrested (Borum 1961). By the time of birth, somatic pre-granulosa cells within the ovary have surrounded oocytes to generate primordial follicles, each consisting of one oocyte (~15 μm diameter in the mouse) enclosed by a single layer of squamous granulosa cells (Findlay et al 2015;Grive and Freiman 2015;Jorgensen 2013;Pepling 2012). However, for reasons not yet fully understood, a significant proportion of the oocyte population is lost by apoptosis during late embryogenesis (Ene et al 2013;Hutt 2015;Malki et al 2014), reducing the number of primordial follicles that form or remain at birth.…”
Section: Overview Of Oogenesis and Folliculogenesismentioning
confidence: 99%
“…We will focus on postnatal growth and development of the oocyte and follicle. We refer readers to recent reviews for studies of pre-and perinatal stages (Findlay et al 2015;Grive and Freiman 2015;Jorgensen 2013;Pepling 2012). Experimental studies have revealed a dynamic bidirectional communication network that links the germ-line and somatic cells of the follicular niche and is governed by both direct cell-cell contact and paracrine signaling.…”
Section: Intra-follicular Cell Contact and Bidirectional Communicationmentioning
confidence: 99%
“…Identifying the underlying mechanisms is particularly challenging in the case of the female, as relatively few oocytes can routinely be obtained for analysis. Nonetheless, because oocytes may remain dormant for up to 50 years in a woman before entering the growth phase that will lead to ovulation and fertilization, and the growth phase itself is a protracted process that requires ∼4 months in humans, they are potentially exposed for a very long time oocyte becomes enclosed by a small number of granulosa cells in a structure termed a primordial follicle [3,7,8]. The ovaries of a newborn female mouse harbor about 8000 primordial follicles [9], and those of a newborn girl about 1,000,000 [10].…”
Section: Introductionmentioning
confidence: 99%